Individual Differences in Working Memory Capacity Modulate Electrophysiological Correlates of Semantic Negative Priming From Single Words - Megías, Montserrat; Ortells, Juan J.; Carmona, Isabel; Noguera, Carmen; Kiefer, Markus (Frontiers in Behavioral Neuroscience, 2021)
In the present study, event-related potentials (ERPs) were registered during a semantic negative priming (NP) task in participants with higher and lower working memory capacity (WMC). On each trial participants had to actively ignore a briefly presented single prime word, which was followed either immediately or after a delay by a mask. Thereafter, either a semantically related or an unrelated target word was presented, to which participants made a semantic categorization judgment. The ignored prime produced a behavioral semantic NP in delayed (but not in immediate) masking trials, and only for participants with a higher-WMC. Both masking type and WMC also modulated ERP priming effects. When the ignored prime was immediately followed by a mask (which impeded its conscious identification) a reliable N400 modulation was found irrespective of participants’ WMC. However, when the mask onset following the prime was delayed (thus allowing its conscious identification), an attenuation of a late positive ERP (LPC) was observed in related compared to unrelated trials, but only in the higher-WMC group showing reliable behavioral NP. The present findings demonstrate for the first time that individual differences in WMC modulate both behavioral measures and electrophysiological correlates of semantic NP.